The socio-ecology of a spotted hyaena Crocuta Crocuta clan in the Kruger National Park - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Thesis (DSc (Zoology))--University of Pretoria, 1986.